2011
DOI: 10.2139/ssrn.1948674
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Tourism Indicators: Selection Criteria for Policy Implementation and Scientific Recognition

Abstract: CIRANO Le CIRANO est un organisme sans but lucratif constitué en vertu de la Loi des compagnies du Québec. Le financement de son infrastructure et de ses activités de recherche provient des cotisations de ses organisations-membres, d'une subvention d'infrastructure du Ministère du Développement économique et régional et de la Recherche, de même que des subventions et mandats obtenus par ses équipes de recherche. CIRANO is a private non-profit organization incorporated under the Québec Companies Act. Its infras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 11 publications
0
44
0
2
Order By: Relevance
“…Community Well-being and Satisfaction: Community well-being ( local satisfaction with tourism; effects of tourism on communities); sustaining cultural assets; attraction protection; crime and harassment; cultural promotion; ownership patterns; resident views (satisfaction); host reactions to tourists; local culture/tradition; community development; social cohesion; sex tourism; community resource; distribution of resource/power; community health and safety; quality of life in general; building/architecture; socio-cultural fabric; recreational quality; address conflicts of interests [27,43,58,93,96,[122][123][124][125]127] Community Participation and Empowerment: Community/resident involvement and participation in tourism; community assets/skills/involvement; uniqueness; community empowerment; cultural education; education and training; equitable changes in local lifestyle; site interpretation; intellectual property; distinction (visit to heritage sites); accessibility; resident access to tourism goods and benefits [27,43,58,93,96,[122][123][124][125]127] Visitor Satisfaction: Tourist satisfaction; visitor management; visitor behavior; accessibility and convenience [27,[122][123][124]128] 4.1.3. Bridging the Global and the Local: Towards a Preliminary Framework…”
Section: Social-culturalmentioning
confidence: 99%
“…Community Well-being and Satisfaction: Community well-being ( local satisfaction with tourism; effects of tourism on communities); sustaining cultural assets; attraction protection; crime and harassment; cultural promotion; ownership patterns; resident views (satisfaction); host reactions to tourists; local culture/tradition; community development; social cohesion; sex tourism; community resource; distribution of resource/power; community health and safety; quality of life in general; building/architecture; socio-cultural fabric; recreational quality; address conflicts of interests [27,43,58,93,96,[122][123][124][125]127] Community Participation and Empowerment: Community/resident involvement and participation in tourism; community assets/skills/involvement; uniqueness; community empowerment; cultural education; education and training; equitable changes in local lifestyle; site interpretation; intellectual property; distinction (visit to heritage sites); accessibility; resident access to tourism goods and benefits [27,43,58,93,96,[122][123][124][125]127] Visitor Satisfaction: Tourist satisfaction; visitor management; visitor behavior; accessibility and convenience [27,[122][123][124]128] 4.1.3. Bridging the Global and the Local: Towards a Preliminary Framework…”
Section: Social-culturalmentioning
confidence: 99%
“…Many studies [69,70] have attempted to list the indicators identified by various research works [71,72] in the field, even defining more than 500 indicators that might be useful for assessing the sustainability of the tourism sector. They tried to create "composite" indicators [69,73] that could provide more immediate methods of evaluation, and improve the usability of the analysis in order to implement strategies for rising sustainability levels.…”
Section: Traditional Indicators In the Field Of Sustainable Tourismmentioning
confidence: 99%
“…Impact is defined as the difference between what would happen with an action and what would happen without it, and can obviously be both positive and negative [70], or both direct and indirect [81].…”
Section: From Heritage Impact Assessment To a Systematic Explicitatiomentioning
confidence: 99%
“…Sustainable tourism development (STD) is a process of meeting the needs of present tourist and host region, whilst protecting and enhancing opportunities for the future (Cernat and Gourdon [3]). However, tourism activities have caused environmental and socioeconomic problems [4]. For this purpose, sustainable tourism principles can help planners to make strategic planning to overcome the problems.…”
Section: Sustainable Tourism Developmentmentioning
confidence: 99%
“…Numerous authors have contributed in providing studies on different perspectives and in different regions. The common purpose for countries to sustain the tourism is to host tourists [3] and protect the environment [4].…”
Section: Introductionmentioning
confidence: 99%